Analisis Faktor-Faktor Yang Berpengaruh Terhadap Keputusan Pembelian Secara Online di Website Tokopedia (Studi Kasus pada Mahasiswa di Universitas Islam Indonesia) - Ardianto Kusuma (Program Studi Manajemen, 2019)
The purpose of this study was to determine the effect of trust, safety, service quality, and risk perception on online purchasing decisions. The population in this study are all consumers who have made purchases through online Tokopedia. The sampling technique in this study using purposive sampling. The requirements to be sampled in this study are those who have made purchases through online Tokopedia. In the sense that the sample is consumers who have made purchases through online Tokopedia within the Indonesian Islamic University students as many as 96 samples. The analytical tool used is Multiple Linear Regression Analysis. The results show that simultaneously the four variables of trust, security, service quality, and risk perception simultaneously have an influence on Online Purchase Decisions on the Tokopedia Website, partially trust has a significant positive effect on Online Purchase Decisions on the Tokopedia Website, partially security has a significant positive effect on Online Purchase Decisions on the Tokopedia Website, partially service quality has a significant positive effect on Online Purchasing Decisions on the Tokopedia Website, and partially risk perceptions have a significant positive effect on Online Purchasing Decisions on the Tokopedia Website